The Effectiveness of The National Collective Management Institute in Song or Music Royalty Management Based on Lawrence M. Friedman's Theory - Intan Dwi Junitasari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This research aims to determine the effectiveness of the National Collective Management Institute in song or music royalty management based on Lawrence M. Frieman's theory. The National Collective Management Institute is a non-State Revenue and Expenditure Budget Government Assistance Agency that is established by the Minister based on the Copyright Law having the authority to withdraw, collect, and distribute Royalties and manage the economic rights interests of Creators and/or Copyright Holders in the field of songs and/or music. The effectiveness of the National Collective Management Institute can be seen in the management of song and/or music royalties owned by the Creator and/or Copyright Holder. The Indonesian Government has issued Government Regulation Number 56 of 2021 concerning the Management of Copyright Royalties for Songs and/or Music, which aims to maximize the function of Management of Copyright Royalties for the use of Works from the Authors and/or Copyright Holders. Based on this research, Government Regulation Number 56 of 2021 concerning the Management of Copyright Royalties for Songs and/or Music, still has not received a positive response from Creators and/or Copyright Holders, due to legal awareness, and socialization related to the management of song royalties and/or music by the National Collective Management Institute is still not performed optimally by the National Collective Management Institute